Climatic limits to headwall retreat in the Khumbu Himalaya, eastern Nepal - Scherler, Dirk (Geology, 2014)
Ice-free bedrock headwalls are widespread landforms of many glacial landscapes, but their formation and evolution are not well understood. Here, I present observations from the Khumbu Himalaya, eastern Nepal, of a distinct elevation zone that aligns the base of many steep headwalls with the highest predicted frost-cracking intensity (FCI). Below this zone, median ice-free hillslope angles are ≤40° and similar to those of other areas in the Himalaya, where threshold hillslopes that are close to the critical angle of stability have been inferred. At higher elevations, ice-free hillslopes of different rock types have median slope angles of ∼50°–55°, suggesting threshold hillslopes with higher rock mass strength, possibly related to the presence of deep-reaching permafrost. High-altitude meteorological data combined with FCI models support frost cracking as a mechanism for headwall retreat by undercutting of threshold headwalls, while glacial transport inhibits the accumulation of scree deposits at their base. This mechanism could account for continued headwall retreat as long as climatic conditions enable frost cracking near the base of headwalls that are high enough to sustain glaciers at their base, even if subglacial erosion is minor. © 2014 Geological Society of America. First published online September 26, 2014. Meteorological data were provided by the National Center for Atmospheric Research (NCAR) Earth Observing Laboratory under sponsorship of the National Science Foundation (http://data.eol.ucar.edu/). Original meteorological data were collected and are provided within the framework of the Ev-K2-CNR and Nepal Academy of Science and Technology Joint Scientific and Technological Research Project, funded by Italian Ministries and National Research Council through the Ev-K2-CNR Committee. ASTER GDEM is a product of the Ministry of Economy, Trade, and Industry of Japan and of NASA. Constructive reviews by R.S. Anderson, T.C. Hales, and D. Burbank helped improve the manuscript.